RELEVANCE OF BUDDHISM IN MODERN WORLD - Dan, Ishwar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The core message of Buddhism centers around peace and integrity. Buddhism is regarded as a practical religion of peace and non-violence. Non-violence is a way of life free from extremes of passion, such as anger, hostility, pleasure, and pain. The principle of non-violence upholds the ideal of universal peace. We come from the land of Buddha, not from the land of War (Yuddh). “Buddhism is not just a religion of the past or a mere faith as many have thought, but it is a time-tested scientific religion and philosophy which, in the context of the present world-situation, is more relevant today than ever before for establishing world peace . In the 21st century, Buddhists have the responsibility to rediscover how their tradition of Ahimsa, love, and compassion can help individuals achieve peace in their own lives and within the global community.